ETIKA WISATAWAN DOMESTIK TERHADAP UPAYA KONSERVASI PANTAI (STUDI KASUS DI PANTAI BALEKAMBANG KABUPATEN MALANG) Ethics of Domestic Tourist to Beach Conservation (Case Study of Balekambang Beach, Malang District) - Atok Miftachul Hudha; Husamah Husamah Husamah (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Abstract: This article is intended to explore the problems of environmental ethics to increase public awareness about the importance of the beach conservation. This research method is descriptive qualitative and quantitave, the primary data was obtained through observation and supported by informants interview. Secondary data were obtained through literature reviews and documents. The data were processed with descriptive techniques. The results of study explained that, (1) The 90 percent of domestic tourists are the resident of East Java, with an age range 1-60 years old, background are very heterogeneous, i.e. worker, farmer, students, researcher, professional, and others. The purpose of going to the beach is also very heterogeneous, which are for a vacation, religious/spiritual, research, economic reason, and others;  (2) The different types of biota which are taken for the purpose of tourists pleasure when they are at the coast are the animal of the phylum Echinodermata; (3) Various organisms which were taken by tourists were not for research purposes but for a moment's pleasure, mostly thrown into the trash due to the damage or rotted as placed in pickup container, and economic factors, The awareness of the importance of conserving marine biota for conservation purposes is very low.